PENGARUH MODEL CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI BERBANTUAN GAMBAR DI SEKOLAH DASAR - Yulianti, Yulianti; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "Whether the model concept to sentence writing skills assisted image description essay grade III primary school Land 01 River Kingdom?," aims to describe how big the influence the application of the model concept sentence against writing skills assisted image description essay Grade III primary school Land 01 River Kingdom. This research uses experimental methods, with the form of a Quasi Experimental Design, types of Non Equivalent Control Group Design. The population of the entire grade III Land 01 River elementary school consisting of 60 students and sampelnya class III B and III C. Data were collected with use of measurement techniques in the form of a written form of essay tests amounted to 1 question.Data obtained average value description essay writing skills by using the model concept sentence (post test) is the control of class 67.20 and average writing skills bouquet description by using the model concept sentence (post test) class experiment is of 74.10. Research results with the test t obtained t_count (2.328) and t _ (table) of 2.017. Because t_count (2.328) ≥ t_tabel (2.017). The magnitude of the influence of the application of the model concept sentence Indonesia language lessons in particular has influence (effect) which is currently in the writing skills bouquet description with the results of the effect size obtained i.e. 0.52 model concept sentence  exert influence are against Garland description writing skills in primary schools of the country 01 River Kingdom.Keywords: Model Concept Sentence, Writing Skills, Essay Description, Pictures.